PENGARUH PERLAKUAN MEDIA PENDINGIN NaCl TERHADAP PELAPISAN PERMUKAAN SURFACE TREATMENT PADA REL KERETA API UIC R54 - Hari Boedi Wahjono; Rafli Rianzah Putra; Willy Artha Wirawan; Fadli Rozaq; Rezki Putra (POLITALA PRESS, 2022)
This study aims to understand and determine how effective the addition of NaCl in the quenching surface treatment media for the UIC R54 railroad. This study applies a method that refers to the theory of surface treatment. First, the surface treatment process is carried out on the surface of the rail specimen. The cooling medium used in the surface treatment process is a mixture of NaCl of 200-800gr NaCl at intervals of 200gr with 1000ml of water. Furthermore, observations of the microstructure and measurement of the hardness value on the surface of the rail specimen were carried out. The average hardness value for raw material specimens is 283.52 BHN. The highest hardness value in specimens that have been surface treated is 346.36 BHN in the treatment of adding 60% NaCl to the quenching medium. In raw material specimens, the phase formed is dominated by ferrite and pearlite. Meanwhile, the phase formed after the surface treatment process is martensite. From these results it can be concluded that a mixture of 60% NaCl with water used as a cooling medium is effective in increasing the hardness value of the rail.